Prediction of postoperative recurrence of perianal fistulizing Crohn’s disease by fecal calprotectin combined with serum miRNA6086 - Shengnan Jin; Maozhen Zhang; Dongdong Gu; Xingping Zhu; Zuolei Wang; Xuerong Shi; Yanping Hao; Su Xu (Journal of International Medical Research)
Objectives This study aimed to identify risk factors for postoperative recurrence in patients with perianal fistulizing Crohn’s disease and assess the predictive value of fecal calprotectin and serum miRNA6086. Methods From 105 patients with perianal fistulizing Crohn’s disease, blood and fecal samples as well as clinical data were collected. Analysis of blood tests, C-reactive protein, miRNA6086, and fecal calprotectin revealed postoperative recurrence risk factors. Receiver operating characteristic curve analysis assessed the predictive accuracy of miRNA6086 and fecal calprotectin for perianal fistulizing Crohn’s disease recurrence and determined their optimal cutoff values, sensitivity, and specificity. Results Of the 105 patients with perianal fistulizing Crohn’s disease, 33 (31.4%) experienced recurrence. Anal fistula type, preoperative miRNA6086, and fecal calprotectin levels were identified as independent risk factors for postoperative recurrence. Receiver operating characteristic curve analysis revealed that miRNA6086 had a cutoff value of 0.3195, sensitivity of 65.28%, specificity of 66.67%, and area under curve value of 0.6589 (95% confidence interval, 0.5503–0.7674). Fecal calprotectin had a cutoff value of 0.6073, sensitivity of 81.94%, specificity of 78.79%, and area under curve value of 0.8224 (95% confidence interval, 0.5503–0.7674). Combined miRNA6086 and fecal calprotectin detection had a cutoff value of 0.7121, sensitivity of 83.33%, specificity of 87.88%, and area under curve value of 0.9146 (95% confidence interval, 0.8547–0.9744). Conclusion Anal fistula type, preoperative miRNA6086, and fecal calprotectin levels are independent risk factors for perianal fistulizing Crohn’s disease recurrence. Combined detection of miRNA6086 and fecal calprotectin levels enhances predictive accuracy for postoperative recurrence.